Africa : Leveraging the Crisis into a Development Takeoff - Devarajan, Shantayanan; Shetty, Sudhir (World Bank, Washington, DC, 2012)
Africa's precise growth and poverty reduction was the result of increased external resources, a buoyant global economy and crucially improved economic policies. Although it is still the world's poorest region, the prospects for resuming growth are good. Additional resources and further policy reforms could launch the continent on a path of sustained growth and poverty reduction. Africa is the world's poorest region and faces development challenges of monumental proportions. Nevertheless, the continents prospects for resuming growth are good because policy reforms generated relative rapid economic growth and poverty reduction before the global crisis, and because policy makers by and large continued to pursue these policies during the crisis. It also means that there is increasing political support for pro-poor reforms the very reforms that will help the continent address the challenges of infrastructure improvement, job creation, governance, and shrinking aid. If the international community continues to support Africa, the combination of additional resources and policy reforms could launch the continent on a path of sustained, rapid growth and poverty reduction.